Probiotic Interventions Alleviate Food Allergy Symptoms Correlated With Cesarean Section: A Murine Model - Jin, Bi-Ying; Li, Zhen; Xia, Ya-Nan; Li, Li-Xiang; Zhao, Zi-Xiao; Li, Xiao-Yu; Li, Yan; Li, Bing; Zhou, Ru-Chen; Fu, Shi-Chen; Li, Shi-Yang; Li, Yan-Qing (Frontiers in Immunology, 2021)
Delivery by caesarean section (CS) is linked to an increased incidence of food allergies in children and affects early gut microbiota colonization. Furthermore, emerging evidence has connected disordered intestinal microbiota to food allergies. Here, we investigated the impact of CS on a rat model for food allergy to ovalbumin (OVA). Rats delivered by CS were found to be more responsive to OVA sensitization than vaginally born ones, displaying a greater reduction in rectal temperature upon challenge, worse diarrhea, and higher levels of OVA-specific antibodies and histamine. 16S rRNA sequencing of feces revealed reduced levels of Lactobacillus and Bifidobacterium in the CS rats. Preventative supplementation with a probiotic combination containing Lactobacillus and Bifidobacterium could protect CS rats against an allergic response to OVA, indicating that the microbiota dysbiosis contributes to CS-related response. Additionally, probiotic intervention early in life might help to rebuild aberrant Th2 responses and tight junction proteins, both of which have been linked to CS-related high allergic reactions. Taken together, this study shows that disordered intestinal microbiota plays an essential role in the pathogenesis of food allergy mediated by CS. More importantly, interventions that modulate the microbiota composition in early life are therapeutically relevant for CS-related food allergies.